Heparin-binding protein as a biomarker of circulatory failure during severe infections: a report of three cases - Beran, Ondrej; Herwald, Heiko; Dzupová, Olga; Chalupa, Pavel; Holub, Michal (Scandinavian journal of infectious diseases, 2010)
We report 3 cases of disease - leptospirosis, tropical malaria and fulminant meningococcaemia - associated with high serum concentrations of heparin-binding protein (HBP) and haemodynamic instability. Furthermore, HBP kinetics were observed for the first 3 days in survivors and were correlated with improvement in clinical condition.
Keywords: Antimicrobial Cationic Peptides; dospělí; Sepsis; Humans; lidé středního věku; sepse; Middle Aged; kationické antimikrobiální peptidy; Shock; transportní proteiny; malárie; mužské pohlaví; Adult; Adolescent; bakteriemie; šok; Bacteremia; biologické markery; ženské pohlaví; krevní proteiny; lidé; Carrier Proteins; mladiství; Biomarkers; Male; Blood Proteins; Malaria; Female